Gluon saturation and proton - Anti-proton cross sections - Carvalho, F.; Durães, F. O.; Luna, E. G S [UNESP] (FapUNIFESP (SciELO), 2007)
We study proton - anti-proton cross sections in the framework of an updated minijet eikonal model. We propose a different scheme for fixing the parameters, in which we make use of the measured minijet cross section. We compare the results obtained with the GRV98, MRST98, CTEQ6-L and KLN gluon distributions. The latter includes gluon saturation effects. We conclude that in the very high energy regime the use of the KLN distribution improves significantly the behavior of the cross sections. However this improvement is due to the shape of the KLN gluon density and has little to do with saturation effects.
Keywords: Gluon saturation; Hadronic cross sections; Minijet eikonal model